PERSEPSI GURU TENTANG PELAKSANAAN SUPERVISI OLEH KEPALA SEKOLAH DI SMK NEGERI SE-KECAMATAN LUBUK BEGALUNGPADANG - INTAN SUCI UTAMA (Jurnal Bahana Manajemen Pendidikan, 2016)
The purpose of this research is to studythe perception of teachers on the implementation of the supervision by the principal at a vocational school in County Down Begalung field. The population was 267 and samples is 81 by using simple random sampling. This research instrument using Likert scale model with a statement that have been tested. Data were analyzed through average. The results of this research is the perception of teachers on the implementation of the supervision by the principal at a vocational school in the bottom Steppe Begalung still in category enough